The Effects of E-Learning on Patient Safety Culture in Emergency Nurses - Tahereh Najafi Ghezeljeh; Razieh Karimpour; Soghra Omrani; Shima Haghani; Azita Emami (Iran University of Medical Sciences, 2021)
Background: Patient Safety (PS) is a priority for all healthcare organizations. Instilling best practices is necessary for PS improvement. This study assessed the effects of Electronic Learning (e-learning) on PS culture among emergency nurses and nursing managers. Methods: This quasi-experimental study was conducted in March-August 2020 using a two-group pre-test, post-test non-randomized design. The study subjects included 69 nurses who were selected from the emergency rooms and 20 nursing managers of two hospitals in Qazvin City, Iran. They were recruited to study through the census sampling method. They were non-randomly allocated to either e-learning or a comparison group. The comparison group received PS-related education through two 1.5-hour lectures on two consecutive days. The experimental group received PS training through a 15-part online course in two months. PS culture was assessed before and 3 months after initiating the intervention. The necessary data were collected through the self-report method using a demographic data questionnaire and the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire. The obtained data were analyzed by Chi-squared test, Fisher's Exact test, Independent-Samples t-test, Paired-Samples t-test, and Analysis of Covariance (ANCOVA) in SPSS. Results: The pre-test mean score of PS culture in the e-learning group was significantly less than that in the comparison group (P=0.002). The mean score of PS culture significantly increased in both research groups after the intervention (P<0.05). Besides, the post-test mean score of PS culture in the e-learning group was significantly greater than that in the comparison group (P<0.001). Conclusion: E-Learning is more effective than conventional lecturing in improving PS culture among emergency nurses. This method is suggested to be used as an effective approach to PS culture improvement among emergency nurses.